Nitrate Assimilation in Leucaena leucocephala Leaves - Pokhriyal, T. C.; Raturi, A. S. (Indian Forester, 1986)
The in vivo Nitrate Reductase activity was standardized for the leaflets of Leucaena leucocephala. The maximum enzyme activity was observed at 7.6 pH (0.05M) and 0.15 M Potassium nitrate concentration. During the study, maximum NR activity (mÂµ moles NO3- reduced g-1 dry wt. h-1) and total NR activity per leaf blade were estimated. In the upper leaf blades followed by a decrease in the subsequent leaf blades in the descending order. Fresh and dry weight values also followed almost the similar trend.